Clinical outcomes of baricitinib in patients with systemic lupus erythematosus: Pooled analysis of SLE-BRAVE-I and SLE-BRAVE-II trials - Juntao Yin; Yantao Hou; Chaoyang Wang; Changjiang Qin (PLoS ONE, 2025)
Background Baricitinib is an oral selective inhibitor of Janus kinase 1/2 that has achieved clinically meaningful outcomes for systemic lupus erythematosus (SLE). Only two phase 3 randomized clinical trials (SLE-BRAVE-I and SLE-BRAVE-II) have been completed, but their conclusions were inconsistent. We aimed to determine the efficacy and safety of once-daily oral baricitinib 4 mg or 2 mg treatment versus placebo in participants with active SLE. Methods SLE-BRAVE-I and SLE-BRAVE-II are two multicenter, placebo-controlled, double-blind, phase 3 randomized clinical trials with follow-up to 52 weeks. At baseline, 1535 patients (aged ≥18 years) with active SLE (excluding those with central nervous system and severe active renal disease) receiving stable background therapy were randomly assigned 1:1:1 to baricitinib 4 mg, baricitinib 2 mg, or placebo once daily for 52 weeks. The primary endpoint was the proportion of patients with an SLE Responder Index (SRI)-4 response at week 52 in the baricitinib 4 mg treatment group compared with placebo. Results There was no difference in the primary efficacy outcome of the proportion of SRI-4 responders at week 52 between participants who received baricitinib 4mg (263 [52%]; odds ratio (OR) 1.27 [95% CI 0.99, 1.63]), 2 mg (246 [48%]; 1.09 [0.85, 1.39]) and placebo (232 [46%]). However, based on SLE-BRAVE-I and SLE-BRAVE-II studies, baricitinib 4 mg and baricitinib 2 mg were more effective in reducing the disease activity in participants who treated with a glucocorticoid dose at baseline of 10 mg per day or higher of prednisone or equivalent, and baricitinib 4 mg was more effective in reducing the disease activity in participants with highly active disease (SLEDAI-2K score at baseline >10). None of the major secondary endpoints, including time to first severe flare and glucocorticoid tapering, were met. Compared with placebo, baricitinib 4 mg and baricitinib 2 mg in the treatment of SLE did not increase the incidence of treatment-emergent adverse events (TEAEs). Conclusions Pooled analysis showed that once-daily oral baricitinib 4 mg or baricitinib 2 mg in addition to SOC did not reduce the overall disease activity compared with placebo although they were safe for SLE. However, baricitinib might be a potential treatment option for SLE in certain subpopulation, such as in participants who received a glucocorticoid dose at baseline of 10 mg per day or higher of prednisone or equivalent (baricitinib 4 mg and baricitinib 2 mg) and in participants with highly active disease (SLEDAI-2K score at baseline >10) (baricitinib 4 mg). Trial registration number ClinicalTrials. gov Registry (NCT03616912 and NCT03616964).